Pengaruh Tingkat Suku Bunga dan Kualitas Pelayanan terhadap Minat Menabung pada PT. Bank Panin Tbk. KCU Bekasi - Negara, Irwanda Sastera; Maulina, Anita (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aims to (a) determine the effect of interest rates on customers' saving trends at Panin Bank Bekasi Main Branch Office. (b) determine the effect of service quality in attracting customers at Panin Bank Bekasi Main Branch Office. (c) determine the effect of interest rates and service quality in encouraging customers to save at Panin Bank Bekasi Main Branch Office. The quantitative research method in this study involves a sample of 90 respondents answering a series of questions with a questionnaire. There is a significant and positive mark between interest rates (X1) and service quality (X2) on customers' interest in saving (Y) of 82.10%.